2012
DOI: 10.1002/uog.11202
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic ovaries at ultrasound: normal variant or silent polycystic ovary syndrome?

Abstract: Objective It is not known whether polycystic ovaries (PCO) levels: 5.25 nmol/L, 4.37 nmol/L and 6.09 nmol/L, respectively). Body mass index, waist circumference and insulin levels had no effect on these differences. Conclusion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 26 publications
2
38
1
2
Order By: Relevance
“…A recent study made a comparison and suggested that the presence of polycystic ovaries upon ultrasound is not a condition that can be considered normal even when it is not associated with this syndrome [22]. In this study, both HR and PCOS patients had a larger number of follicles after hormonal stimulation than the control group, which appears to not be a physiological condition.…”
Section: Discussionmentioning
confidence: 81%
“…A recent study made a comparison and suggested that the presence of polycystic ovaries upon ultrasound is not a condition that can be considered normal even when it is not associated with this syndrome [22]. In this study, both HR and PCOS patients had a larger number of follicles after hormonal stimulation than the control group, which appears to not be a physiological condition.…”
Section: Discussionmentioning
confidence: 81%
“…On the other hand, some studies have revealed that women having isolated PCO, unlike those with PCOS, do not have altered endocrine and metabolic profile compared to normal controls [12,15,23]. As limited by the retrospective nature of our current study, however, we did not have the metabolic and endocrine data for comparison among the three groups.…”
Section: Discussionmentioning
confidence: 82%
“…Some hypothesize that PCO alone constitutes the mildest form of PCOS as these women showed intermediate serum anti-Mullerian hormone levels 35 and responses to a gonadotropin-releasing hormone challenge 36 compared to women with Frank PCOS and controls. We noted that women with PCO alone did not differ from controls in their metabolic profile, consistent with previous reports, 12,35 but in contrast to others showing subtle variations in insulin sensitivity and androgen levels. [36][37][38][39][40] It is difficult to fully appreciate discrepancies between studies since they failed to report actual follicle counts or other sonographic end points for their cohorts.…”
Section: Discussionmentioning
confidence: 99%